Mental fatigue in sport - from impaired performance to increased injury risk - Schampheleer, E.; Roelands, B. (International Journal of Sports Physiology and Performance, 2024)
The literature describing the effects of mental fatigue (MF) has grown tremendously. This is accompanied by identification of a host of performance-determining parameters affected by MF. MF results from prolonged cognitive effort and predominantly affects physical, technical, tactical, and perceptual-cognitive dimensions of sport, while physiological parameters (eg, heart rate, lactate) and physical aspects of maximal and supramaximal efforts are predominantly unaffected. The aim of this paper was to provide an overview of the parameters described in the literature as influenced by MF. By identifying the different parameters, we not only see how they affect the performance of athletes but also raise concerns about the potentially increased injury risk due to MF. Preliminary evidence suggests that subsequent disturbances in balance, motor skills, and decision-making processes could potentially increase the vulnerability to injury. An abundance of lab-based studies looked into the effects of MF on performance; however, many questions remain about the mechanisms of origin and neurophysiological causes of MF, and only small steps have been taken to translate this knowledge into practice. Thus, there is a need for more research into the underlying mechanisms of MF and the role of the brain, as well as more applied research with a high ecological validity that also takes into account the potential increased risk of injury due to MF.